Determinants of Production Risk in Cauliflower Farming Using the Just and Pope Production Function Model in Tanggamus Regency - Fembriarti Erry Prasmatiwi; Dwi Haryono; Fika, Rafika Dila Putri (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Cauliflower is a horticultural commodity vulnerable to production risks caused by pest and disease infestations and climate change, along with risks inherent in the use of farming production factors. This crop is an emerging commodity in Tanggamus Regency, Lampung Province. The study aims to measure the magnitude of production risks, and determinants of production risk in cauliflower farming in Tanggamus Regency. The research was conducted in the Gunung Alip and Gisting districts, as they represent the sole areas of cauliflower cultivation in Tanggamus. Data were collected from 74 cauliflower farmers during the 2024 dry season, from January to August 2025. Production risk was measured using the coefficient of variation (CV). The determinants of production risk were analyzed using the Just and Pope production function approach. The findings indicate a coefficient of variation of 0.27, which signifies a low level of risk in cauliflower farming. Factors that significantly affect production include land area, seeds, NPK fertilizer, manure, and labor. Factors that significantly affect production include land area, seeds, NPK fertilizer, manure, and labor. Among the inputs, pesticide use increases production risk, whereas the use of seeds significantly reduces it.